Analisis Sekuen DNA Mitokondria Cytochrome Oxidase I (COI) mtDNA Pada Kukang Indonesia (Nycticebus spp) sebagai Penanda Guna Pengembangan Identifikasi Spesies - Wirdateti, Wirdateti; Indriana, Eka; Handayani, Handayani (JURNAL BIOLOGI INDONESIA, 2016)
Slow lories is small size primates of the genus Nycticebus that are in endangered status. Habitat pressure andhigh trade as pet animals has made the population decline both quantitatively and qualitatively, therefore it isnecessary to save the slow lories through conservation action. Morphologically, the individuals are difficult tobe distinguished among the species, therefore making much harder in identification for conservation purposessuch as from confiscated individuals. Therefore molecular marker is needed through mitochondrial DNA usingCOI gene sequences analysis is needed for identification. This study used 24 samples of slow lories consistedof 2 from Kalimantan, 9 from Java and 13 from Sumatra. The result indicated that in the 660 bp there were 62variable sites with 15 haplotypes: 4 haplotypes of N. javanicus, 9 haplotypes N. coucang, and 2 haplotypes N.menagensis. Base on nucleotide variations at specific sites, it was formed haplotype differences among species.The average genetic distance between species showed that Kalimanatan population were closer to thepopulation of Sumatra (d= 0.042 Â± 0.006) compared with Java population (d= 0.059 Â± 0.009), whereas thegenetic distance within population showed the population of Java had low diversity (d= 0.002) with a meannucleotide differences 2.6. Thus Jawan slow loris (N. javanicus) should be conserved.Keywords: Nycticebus spp., molecular, COI, conservation, marker